A Review of Supernumerary Teeth in the Premolar Region - Khaled Khalaf; Saaid Al Shehadat; Colin A. Murray (International Journal of Dentistry)
Supernumerary teeth in the premolar region, unlike other supernumeraries, occur more often in the mandible where they are generally of the supplemental type. Occasionally, they are conical or smaller than normal, particularly in the upper premolar regions. They might occur singly or in multiples, be erupted or impacted, but the majority have been found to be unerupted and asymptomatic. The prevalence of supernumerary teeth in the premolar region has been demonstrated to be between 0.01 and 1 percent depending on the population studied. Interestingly, populations from the East or Africa are known to be the most affected. Various theories have been suggested to explain the etiology of supernumerary teeth in general including both genetic and environmental factors. Furthermore, it has been suggested that supernumerary premolar teeth belong to a third (postpermanent) series, developing from extensions of the dental lamina. Several consequences can result from the presence of supernumerary premolars, especially in the mandible, such as cyst formation, transposition, and other clinical scenarios.